2020
DOI: 10.3390/molecules25040869
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant Activity of Pastinaca sativa L. ssp. sylvestris [Mill.] Rouy and Camus Essential Oil

Abstract: In the last decade, there has been growing interest in the food industry in replacing synthetic chemicals with natural products with bioactive properties. This study’s aims were to determine the chemical composition and the antioxidant properties of the essential oil of Pastianica sylvestris. The essential oil was isolated with a yield of 0.41% (w/v) by steam distillation from the dried seeds and subsequently analysed by GC-MS. Octyl acetate (78.49%) and octyl hexanoate (6.68%) were the main components. The es… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 30 publications
0
15
0
Order By: Relevance
“…The new radicals generated by the loss of a hydrogen atom from the diallylic methylene groups attack the unsaturated β-carotene molecules, which they oxidize and partially decompose [ 59 ]. The rate of β-carotene discoloration can be decreased in the presence of antioxidants [ 31 , 60 ]. The relative antioxidant activity (RAA) of MSEO was calculated according to the following equation: RAA = A MSEO /A BHT , where A BHT is the absorption of BHT (positive control used) and A MSEO is the absorption of MSEO.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The new radicals generated by the loss of a hydrogen atom from the diallylic methylene groups attack the unsaturated β-carotene molecules, which they oxidize and partially decompose [ 59 ]. The rate of β-carotene discoloration can be decreased in the presence of antioxidants [ 31 , 60 ]. The relative antioxidant activity (RAA) of MSEO was calculated according to the following equation: RAA = A MSEO /A BHT , where A BHT is the absorption of BHT (positive control used) and A MSEO is the absorption of MSEO.…”
Section: Resultsmentioning
confidence: 99%
“…The thiobarbituric acid (TBA) test, as described by Jianu et al [ 31 ], was adopted; briefly, 2 g of each sample, benzene (5 mL), and 0.67% aqueous thiobarbituric acid solution (4 mL) were mixed and continuously homogenized for 1 h with a mechanical shaker. Subsequently, the supernatant was maintained on a hot water bath for 45 min.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Another study of phenolic content conducted some plant ethanolic extracts showed that phenolic content worked in this study may be good antioxidant agent (Koley et al, 2016). A study showed that Pastinaca genus shows phenolic content (Jianu et al, 2020). Therefore, P. zozimoides may be consumed as a natural source for antioxidant phenols and be attributed health benefits.…”
Section: Total Phenolic Contentmentioning
confidence: 62%
“…Antioxidants can scavenge these free radicals to reduce cellular damage and prevent different diseases. Because of their beneficial effects on human health, there is widespread interest in antioxidants in both pharmaceutical and food science [35,36]. We tested the antioxidant activity of the synthetic chitosan derivatives (Figures 3-5) and very satisfactory results had been achieved.…”
Section: Antioxidant Activitymentioning
confidence: 97%